Researcher Profile: An Interview with Joseph Goetz, Ph.D. (Journal of Financial Therapy, 2010)
Dr. Joseph Goetz is an internationally known researcher working in academia to blend financial planning, financial counseling, and therapy approaches into tools and techniques that enhance the well-being of individuals and families. Dr. Goetz’s work in developing the ASPIRE clinic at the University of Georgia has helped place Georgia at the forefront of financial therapy research. In this interview readers of the Journal can learn more about the exciting work Dr. Goetz is doing to advance the Financial Therapy profession.
Keywords: financial Planning; marriage and family therapy